Analysis of the Hotspots and Trends of New-media Ideological and Political Research: Citespace Visual Analysis Based on the Literature from 2012 to 2021 - Dongjie, Wu; Yonggang, Zhang; Sisi, Huang (SHS web of conferences, 2023)
Nowadays, the rapid development of Internet technology and the wide application of new media technology have brought unprecedented challenges and opportunities to the ideological and political work in colleges and universities. Against this background, promoting the high integration of traditional advantages of ideological and political work with information technology is conducive to enhancing ideological and political education’s keeping pace with the times and its appeal. To this end, based on the analysis of Citespace visual data of related literature from 2012 to 2021, this research investigates the frontier hotspots and theoretical focus of new media ideological and political research in China. As a whole, the discussion on the research trend of ideological and political work based on the new-media environment reveals that future related research will focus on the new-media turn of traditional ideological and political work, encompassing the transformation of concepts, the innovation of paths, as well as the cultivation of talent teams.